Development of real-time PCR methods for quality control detection of pathogenic bacteria in cosmetic preparations - Bolzon, Veronica; Bulfoni, Michela; Nencioni, Alessandro; Nencioni, Emanuele (Frontiers in Public Health, 2025)
IntroductionThe preservation of microbial safety in cosmetic products is essential for consumer health and requires rapid and accurate detection strategies… Traditional detection methods, such as quantitative and qualitative tests, are effective but often time-consuming and labor-intensive. Moreover, plate count methods fail to detect viable but non-cultivable cells, which remain alive but cannot grow under standard laboratory conditions. To address these limitations, molecular techniques like PCR, particularly real-time PCR (rt-PCR), multiplex rt-PCR, and viability PCR assays, as well as flow cytometry, have enhanced microbiological analysis by improving detection sensitivity, accuracy, and enabling rapid pathogen identification. ISO standards offer guidelines for reliable and consistent microbial detection methods, to guarantee the effectiveness of traditional and molecular techniques in food and cosmetic safety testing.MethodsThis study evaluates real-time PCR (rt-PCR) as an alternative to the traditional plate-based method for the detection of Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa, and Candida albicans in cosmetic formulations.Results and discussionrt-PCR consistently demonstrated superior sensitivity and reliability, particularly in detecting pathogens at low inoculum levels and within complex matrices. For all pathogens, rt-PCR achieved a 100% detection rate across all replicates, reaching the same or superior results than the classical plate method. rt-PCR’s ability to directly target DNA overcomes issues related to colony morphology and microbial competition. The study highlights the necessity of standardized rt-PCR protocols aligned with international ISO guidelines to enhance its applicability in routine quality control programs. In conclusion, rt-PCR represents a significant advancement in microbial safety for food and cosmetics, offering a rapid, sensitive, and reliable alternative to conventional methods. By integrating enrichment strategies, rt-PCR ensures higher accuracy in pathogen detection, reinforcing product safety and regulatory compliance in the cosmetics industry.